Application of capsule endoscopy in patients with chronic and recurrent abdominal pain: Abbreviated running title: capsule endoscopy in abdominal pain. (December 2022) - Yang, Wei; Li, Zheng; Liu, Rui; Tong, Xudong; Wang, Wei; Xu, Dongqiang; Gao, Shan
Highlights: Capsule endoscopy has a great value in the diagnosis of chronic and recurrent abdominal pain with satisfactory safety and less pain for patients. Inflammatory lesions and small intestine ulcers were the predominant reasons for unexplained and recurrent abdominal pain. Parasite, polyp, diverticulum and vascular malformation occupied a certain proportion. The lymphangiectasia of small intestine was less frequently observed. Abstract: Objective: The incidence of chronic and recurrent abdominal pain increases every year, while the diagnosis is still unsatisfactory even after a number of check-ups. This study aimed to evaluate the diagnosis value of capsule endoscopy in patients suffering from chronic and recurrent abdominal pain. Methods: A retrospective case study was performed in 80 chronic and recurrent abdominal pain patients at Xiangyang Central Hospital from January 2013 to November 2017. Meanwhile, diagnoses by capsule endoscopy were collected for analysis. Results: Abnormal findings were found in 54 of 80 (67.5%) patients. The findings in chronic and recurrent abdominal pain patients include small intestinal erosion and congestion, small intestinal ulcers, small intestinal parasites, small intestinal vascular malformations, small intestinal polyps, small intestinal diverticulum, and small intestinal lymphangiectasia. There were no immediate significant side effects without being reported up to 1 month after ingestion of the capsule. The capsule was evacuated by all patients. Conclusions: Capsule endoscopy has a great value in the diagnosis of chronic and recurrent abdominal pain with satisfactory safety and less pain for patients. Inflammatory lesions and ulcers in the small intestine account for the majority of positive findings in these patients.